An Experimental Study of Low-Frequency Wave Dispersion and Attenuation in Water Saturated Sandstones - Mikhaltsevitch, Vassili; Lebedev, Maxim; Gurevich, Boris (American Society of Civil Engineers, 2013)
The elastic and anelastic parameters of dry and distilled water-saturated sandstones with low (~7.8 mD) and high (~590 mD) permeabilities were measured at various confining pressures and room temperature (22° C). The both sandstones were quarried in Donnybrook, Western Australia. The experiments were performed with a new laboratory apparatus utilizing stress-strain relationship, which was developed to measure the complex Young's moduli of rocks at seismic (1-100 Hz) and teleseismic (≤1 Hz) frequencies, confining or uniaxial pressures from 0 to 70 MPa, and strain amplitudes 10-8-10-7. The measurements in water-saturated sandstones reveal a prominent peak of attenuation in the sample with low permeability at frequency ~0.8 Hz, whereas the attenuation in the high permeable sample remains similar to the attenuation measured under dry conditions. These results demonstrate that for low-permeability rocks seismic frequencies do not necessarily correspond to the low frequency limit of acoustic wave dispersion.